Heteronuclear dipolar decoupling effects on multiple-quantum and satellite-transition magic-angle spinning NMR spectra - Ganapathy, Subramanian; Delevoye, L.; Arnoureux, J. P.; Madhu, Perunthiruthy K. (Magnetic Resonance in Chemistry, 2008)
We here report on the influence of heteronuclear dipolar decoupling on the Al-27 3QMAS, 5QMAS, and the double-quantum filter-satellite-transition magic-angle spinning (DQF-STMAS) spectra of a strongly dipolar-coupled system, gibbsite. The requirements for heteronuclear dipolar decoupling increase with the order of coherence evolving in the indirect dimension of a two-dimensional (2D) experiment. The isotropic line width of the high-resolution 2D spectra, in samples like gibbsite, is composed of four parts: the distribution of isotropic shifts (delta(ISO), delta(QIS)), the homogeneous broadening related to the proton-proton flip-flop terms, the Al-27-Al-27 homonulcear dipolar couplings, and the H-1-Al-27 heteronuclear dipolar couplings. It is shown that, even in the case of gibbsite, where a strong proton-proton bath exists, the main resolution limiting factor in these experiments resides in the H-1-Al-27 dipolar interaction. Copyright (C) 2008 John Wiley & Sons, Ltd.
Keywords: heteronuclear broadening; heteronuclear decoupling; homogeneous broadening; MQMAS; quadrupolar nuclei; Solid-state NMR; STMAS; TPPM

Evidence for the co-existence of distorted tetrahedral and trigonal bipyramidal aluminium sites in SrAl12O19 from Al-27 NMR studies - Harindranath, K.; Viswanath, K. Anusree; Chandran, C. Vinod; Braeuniger, Thomas; Madhu, Perunthiruthy K.; Ajithkumar, Thalasseril G.; Joy, Pattayil Alias (Solid State Communications, 2010)
Strontium aluminate, SrAl12O19, is a ceramic material having the hexagonal magnetoplumbite-type structure, with multiple Al coordination environments. An earlier low-field Al-27 solid-state NMR study reported five different Al sites in this system: one AlO4, one AlO5, and three AlO6 sites; whereas a later high-field study showed that the AlO5 site is a distorted AlO4 site with a very large quadrupolar coupling constant (similar to 20 MHz). Our magic angle spinning (MAS) and 3-quantum magic angle spinning (3QMAS) NMR studies at 7.05 T unambiguously show evidence for an AlO5 site. However, evidence for the presence of a distorted AlO4 site is obtained from studies at high fields (16.4 and 17.6 T), in addition to the AlO5 site. Thus the present solid-state NMR studies give evidence for the simultaneous presence of both the five-coordinated and distorted four-coordinated sites in this system. (C) 2009 Elsevier Ltd. All rights reserved.
Keywords: Local structure; MQMAS; Nuclear magnetic resonance; Strontium aluminate